Dynamic random lasing in silica aerogel doped with rhodamine 6G (vol 8, pg 29678, 2018) - Wetter, Niklaus Ursus (2018)
CNEN IPEN SP, Ctr Lasers & Aplicacoes, Ave Prof Lineu Prestes 2242, BR-05508000 Sao Paulo, Brazil